Federal Mortgage Interest Rate Policy and the Supply of FHA-VA Credit - Schaaf, Albert H. (The Review of Economics and Statistics, 1958)
IN recent years, the underwriting of residential mortgage loans by the Federal Housing Administration (FHA) and Veterans Administration (VA) has become an increasingly important device for implementing federal housing policy.' The government's assumption of the major risks of mortgage default through FHA insurance and VA guarantee has encouraged private lenders to extend loan terms that have greatly magnified the purchasing power of the house buyer's down-payment and monthlypayment dollars. The resulting ability of the government to augment and channel effective demand has been used in various ways. Aggregative policies have been aimed at improving national housing standards by stimulating a high level of residential construction and widening the private industry's market. Special programs have been designed to place certain groups in preferential market positions. Veterans, owners wishing to rehabilitate deteriorated properties, and low income families displaced by slum clearance projects are examples of such groups. Throughout the postwar period, however, these programs have been hampered by intermittently recurring credit shortages, particularly those programs which depended on the more liberal-term loans. Such shortages were most acute in I948-49, I95I-53, and I956-57, and in areas farthest removed from the money markets of the Northeast. In each instance the credit difficulties have resulted in widespread controversy over the federal government's mortgage interest rate policy. On both insured and guaranteed loans, the government has established the maximum interest rates which may be charged the borrower. The principal aim has been to fix a rate which would reduce as far as possible the costs of home financing and at the same time encourage a satisfactory volume of private lending. Such encouragement is of the utmost importance, since normally both the FHA and VA rely fully upon private lenders for the provision of insured and guaranteed credit. This article undertakes to analyze the relationship between FHA-VA interest rates and the supply of insured and guaranteed mortgage funds. Based on an analysis of the postwar experience we shall attempt to determine the degree to which the government's mortgage interest rate policy can augment the supply of these funds and what constitutes an effective policy for this purpose given the twin objective of reducing home financing costs.